Pengaruh Suhu dan Waktu Pengeringan Terhadap Karakteristik Serbuk Pewarna Instan Daun Singkong (Manihot utilissima Pohl.) - Andini, Yustina; Diah Puspawati, Gusti Ayu Kadek; Mayun Permana, I Dewa Gde (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i04.p07, 2023)
Natural dyes can be used as an alternative to minimize the negative effects of using synthetic dyes. One type of natural dye that can be used is cassava leaves, because cassava leaves have a fairly high chlorophyll, namely 27.446 mg/g. The purpose of this study was to determine the effect temperature and time of drying to produce instant dye powder from cassava leaves. The research design used was factorial completely randomized design with drying temperature treatment consisting of 3 levels: (50 ?C, 60 ?C and 70 ?C) and drying time treatment with 3 levels: (4 hours, 5 hours and 6 hours). This study was repeated 2 times to produce 18 experimental units. The data were analyzed by analysis of variance, if the treatment had a significant effect, it was continued with Duncan's Multiple Range Test. The results showed that the interaction of temperature and drying time significantly affected the yield, moisture content, ash content, total chlorophyll, solubility, solubility time and brightness level (L*) of cassava leaf instant dye powder. The characteristics of the best cassava leaf instant dye powder were obtained at a drying temperature of 50 ?C and a drying time of 4 hours with a yield of 9.73%, water content 7.29%, ash content 0.75%, total chlorophyll 9.86 mg/g, solubility 42.96%, and color with criteria of brightness (L) 27.10, greenish (a*) - 33.80 and yellowish (b*) 9.00.